(NwYSOKOMAGNEZIALXNYJ MAGMATIZM RANNEGO DOKEMBRIQ (B/s - (NkULIKOW(B, (NwQ^ESLAW sTEPANOWI^s; (NiN(B-(NT GEOLOGII kARELXSKOGO FIL(B. (Nan sssrs ((NpETROZAWODSK (B:s (Nb(B. (NI(B.,s, 1989)
\(NbIBLIOGR(B. (NW KONCE DOKL(B.s
Keywords: (NdOKEMBRIJSKIE OTLOVENIQ (B- (NsBORNIKIs; (NmAGMATIZM (B- (NsBORNIKIs